Greenland, view of Kjerulf Fjord and Hisinger Gletscher - Boyd, Louise Arner, 1887-1972 (1931)
August 2, 1931. Kjerulfs [Kjerulf] Fjord. Left Valley. In background: L.A.B.'s Currycomb Peak forming west side. In foreground on extreme left; mound of dirt. This is moraine from one of the points. Hisinger Glacier [Hisinger Gletscher] extends into south end of Left Valley. Hisinger Glacier [Hisinger Gletscher], at what L.A.B. calls The Divide, widens out, spills over into scoops and points --extending these into the southern end of Left Valley. This photo is No. 21 of pan C --and the point of Hisinger Glacier [Hisinger Gletscher] shows in No. 16 of pan C. In foreground on right; pond-like lake, sourced from waters of Hisinger Glacier [Hisinger Gletscher]; from lake stream goes down Left Valley and beyond into Kjerulfs [Kjerulf] Fjord. Photo taken on east side of Left Valley, looking W.N.W.